Environment as a Complex System: the Malaria Decrease in the Legal Amazonia (LA) Case - Kamimura, Arlindo; Burani, Geraldo; Sauer, Ildo (Interações, 2018)
In Brazil, malaria is an endemic disease present mainly in the Legal Amazon (LA), which accounts for more than 99% of the country´s cases. In 2000 the number of new cases of malaria in LA was 613.3 thousand, decreasing to 265.4 thousand cases in 2011, thus dropping by 56.7%. The malaria system behavior depends on many interrelated variables and environmental factors, constituting itself in a complex, non-linear dynamical living system, whose resulting dynamics have as main characteristics the unpredictability and the extreme sensitivity to the initial conditions. This paper is an investigation of a possible additional cause for the huge decrease in cases of malaria in the states of LA, in addition to the already recognized governmental effort to malaria disease control. The hypothesis adopted is that all domestic animals (exception fowls) compete with the man in the position of hosts feeding of the mosquito Anopheles, vector-borne of the disease.